2012
DOI: 10.1016/j.jfluidstructs.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Numerical quantification of aerodynamic damping on pitching of vehicle-inspired bluff body

Abstract: The influence of transient flows on vehicle stability was investigated by large eddy simulation. To consider the dynamic response of a vehicle to real-life transient aerodynamics, a dimensionless parameter that quantifies the amount of aerodynamic damping for vehicle subjects to pitching oscillation is proposed. Two vehicle models with different stability characteristics were created to verify the parameter. For idealized notchback models, underbody has the highest contribution to the total aerodynamic damping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 33 publications
(38 reference statements)
0
25
1
Order By: Relevance
“…Cheng et al (2011) reported that the aerodynamic effect due to the trailing vortices shed from the front pillar (which correspond to the A-pillar in the case of sedan-type passenger car) tended to destabilize the model's pitching oscillation, while the aerodynamic effect due to the trailing vortices shed from the rear pillar (which correspond to the C-pillar) tended to stabilize it. Hence, the model with rounded front pillar and angular rear pillar exhibited a significantly higher aerodynamic damping than the model with the opposite pillar shape configurations (Cheng et al, 2012).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Cheng et al (2011) reported that the aerodynamic effect due to the trailing vortices shed from the front pillar (which correspond to the A-pillar in the case of sedan-type passenger car) tended to destabilize the model's pitching oscillation, while the aerodynamic effect due to the trailing vortices shed from the rear pillar (which correspond to the C-pillar) tended to stabilize it. Hence, the model with rounded front pillar and angular rear pillar exhibited a significantly higher aerodynamic damping than the model with the opposite pillar shape configurations (Cheng et al, 2012).…”
Section: Introductionmentioning
confidence: 83%
“…To overcome these limitations, therefore, we have developed in the earlier phase of the study a numerical method which can resolve the spatial and temporal details of the flow properties, for the assessment of vehicle aerodynamic stability performance in a transient driving situation (interested reader is referred to Nakashima et al (2009) and Cheng et al (2011, 2012). In regard to the aerodynamic stability performance of vehicles, most studies reported in the literature were focus on yawing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, it helps to provide insight into how each spoiler configurations would perform under a more realistic driving condition if certain motion mode could be incorporated in the flow simulation. For this purpose, the method introduced by Cheng et al [10,11] could be employed in the future studies.…”
Section: Discussionmentioning
confidence: 99%